2016
DOI: 10.3892/ijo.2016.3692
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles shed by melanoma cells contain a modified form of H1.0 linker histone and H1.0 mRNA-binding proteins

Abstract: Extracellular vesicles (EVs) are now recognized as a fundamental way for cell-to-cell horizontal transfer of properties, in both physiological and pathological conditions. Most of EV-mediated cross-talk among cells depend on the exchange of proteins, and nucleic acids, among which mRNAs, and non-coding RNAs such as different species of miRNAs. Cancer cells, in particular, use EVs to discard molecules which could be dangerous to them (for example differentiation-inducing proteins such as histone H1.0, or antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Together with these different classes of RNA, EVs also contain RNA-binding proteins (RBPs) [160,161]. Given the known role of these latter proteins in the sub-cellular RNA localization, it has been suggested that during vesicle biogenesis RBPs can regulate accumulation of selected RNAs into vesicles [161][162][163].…”
Section: Evs In the Nervous System: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with these different classes of RNA, EVs also contain RNA-binding proteins (RBPs) [160,161]. Given the known role of these latter proteins in the sub-cellular RNA localization, it has been suggested that during vesicle biogenesis RBPs can regulate accumulation of selected RNAs into vesicles [161][162][163].…”
Section: Evs In the Nervous System: General Considerationsmentioning
confidence: 99%
“…Loss of the lysosomal kinesin adaptor ADP-ribosylation factor-like protein 8 (Arl8) causes accumulation of both synaptic vesicles and AZ-protein-containing vesicles in the neuronal body, with the consequent alteration of the presynaptic structures and impairment of neurotransmission [168]. Super-resolution microscopy and live imaging have also Together with these different classes of RNA, EVs also contain RNA-binding proteins (RBPs) [160,161]. Given the known role of these latter proteins in the sub-cellular RNA localization, it has been suggested that during vesicle biogenesis RBPs can regulate accumulation of selected RNAs into vesicles [161][162][163].…”
Section: Evs In the Nervous System: General Considerationsmentioning
confidence: 99%
“…2325 These proteins were included because transferrin is a typical abundant serum protein, apoE was reported as an EVs-associated regulatory protein, 26 and there are reports supporting the presence of histones in EVs. 27,28 The data in pmol of targeted protein per mg of the total protein in EVs(208K) and EVs(SEC) representative preparations are shown in Figure 3. Since the dynamic range of targeted proteins is approximately 10 5 , the data for a representative experiment are shown in two separate groups with different y -axis scales.…”
Section: Resultsmentioning
confidence: 99%
“…RBP also account for localization and trafficking of RNA-protein complexes in cells (115,116). Finally, the mRNA profile of Exo differs from that of cells (117), metabolic enzymes and proteins engaged in cell-cell and cell-matrix adhesion being frequently overrepresented (118)(119)(120), and possibly translated in Exo (121,122).…”
Section: Exosome Compositionmentioning
confidence: 99%